Experimental research on affecting factors of the cutting quality of sugarcane harvesters under complicated excitations - Mo, Hanning; Ma, Shaochun; Qiu, Chen; Huang, Zhimin; Li, Shangping (International Journal of Agricultural and Biological Engineering, 2024)
The sugarcane field excitation, cutting forces and the engine excitation constitute complicated excitations acting on sugarcane harvesters. In this study, the sugarcane cutting mechanism under complicated excitations was analyzed. The dynamics and the mathematical models of sugarcane harvesters were established and simulated. Based on theoretical analysis, sugarcane cutting experiments were done on a self-built sugarcane harvester test platform (SHTP), designed as single-factor and the orthogonal experiments. Effects of the sugarcane field excitation characterized by the sugarcane field excitation device (SFED) output frequency, the engine excitation characterized by the actuating engine output frequency, the cutter rotating speed, the sugarcane harvester travelling speed simulated through the sugarcane transporting speed of the SHTP and the cutter inclination angle on the cutting quality of sugarcane harvesters were studied. Effects of the axial cutter vibration on three-directional cutting forces and the sugarcane cutting quality (SCQ) as well as effects of three-directional cutting forces on the SCQ were further studied. It is shown that the sugarcane field excitation, the axial cutter vibration amplitude and frequency as well as the three-directional cutting forces have significantly negative monotonic correlated effects on the SCQ while the cutter rotating speed, the sugarcane harvester travelling speed and the cutter inclination angle have significantly positive monotonic correlated effects on the SCQ. Significance levels of effects on three-directional cutting forces and the SCQ form high to low are as follow, the axial cutter vibration, the sugarcane field excitation, the cutter rotating speed, the engine excitation, the cutter inclination angle, the sugarcane harvester travelling speed. The theoretical analysis results were verified through experiment and an optimal combination was obtained with the cutter rotating speed of 700 r/min, sugarcane harvester travelling speed of 0.6 m/s and cutter inclination angle of 8º. This study can provide a reference for setting cutting parameters of sugarcane harvesters with a good SCQ. Keywords: sugarcane harvester, cutting quality, complicated excitations, experimental research, theoretical analysis DOI: 10.25165/j.ijabe.20241705.8142 Citation: Mo H N, Ma S C, Qiu C, Huang Z M, Li S P. Experimental research on affecting factors of the cutting quality of sugarcane harvesters under complicated excitations. Int J Agric & BIol Eng, 17(5): 176-192.